Studies on the computer processing and understanding of Malay language text - Ahmad Zaki Abu Bakar, 1956-, author; Mohamad Arif Nun, supervisor; Fakulti Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 1989)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 1989